Current challenges to multinational federalism in India - Adeney, Katharine; Bhattacharyya, Harihar (Taylor & Francis, 2018)
India’s multinational federation has experienced multiple challenges in the last 25 years, relating to the rise of coalition politics and the process of economic liberalisation, both of which have increased the power of some of the states of the federation at the expense of others. The internal borders of India continue to be restructured, with the latest state, Telangana, created in 2014. India is often seen as a successful multinational federation but it is important to recognise the limitations of this success, as well as the areas where the rise of an aggressive Hindu nationalism poses a powerful threat to India’s multinational federal democracy.